Anatomical and Physiological Responses of M5 Mutant Red Rice G16 from Gamma Irradiation to Drought Stress Condition in Vegetative Phase - Chandraningsih, Ria Ayu; Sudharmawan, A.A.K.; Suliartini, Ni Wayan Sri; Fauzi, M. Taufik; Yakop, Uyek Malik (Pascasarjana, Mataram University, 2024)
Food security and sustainability are facing challenges due to the increase in population and the large amount of dry land that has not been optimized for utilization. Rice cultivated in paddy fields is a problem that must be considered. The use of local varieties should be further studied because it is one of the efforts to increase plant productivity against drought stress. This study aims to assess the anatomical and physiological responses of M5 mutant G16 red rice from gamma irradiation to drought stress in the vegetative phase. The method used was experimental method with field experiments. The experiment was conducted from November 2023 to July 2024 at the Greenhouse of the Faculty of Agriculture, University of Mataram. The experimental design used was Faktorial Completely Randomized Design (CRD) with two factors, the first factor is drought stress consisting of 33% Field Capacity (K1), 66% Field Capacity (K2), 100% Field Capacity (K3) and the second factor is genotype consisting of Inpago Unram (P1), MD200-G13-18-16 (P2), MD300-G20-16-9-5 (P3), MD200-G24-17-10 (P4), MD300-G27-8-3-5 (P5). The result of this study show that MD200-G24-17-10 (P4) was the most responsive genotype to drought stress conditions in the vegetative phase. This was indicated by a decrease in stomatal density and chlorophyll content, as well as an increase in xylem diameter and stele diameter.